2021
DOI: 10.3390/ijms23010265
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of AIF/CypA Lethal Pathway in SH-SY5Y Cells Treated with Staurosporine

Abstract: The AIF/CypA complex exerts a lethal activity in several rodent models of acute brain injury. Upon formation, it translocates into the nucleus of cells receiving apoptotic stimuli, inducing chromatin condensation, DNA fragmentation, and cell death by a caspase-independent mechanism. Inhibition of this complex in a model of glutamate-induced cell death in HT-22 neuronal cells by an AIF peptide (AIF(370-394)) mimicking the binding site on CypA, restores cell survival and prevents brain injury in neonatal mice un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For the functional prediction, the overlapping pathway, enriched staurosporine biosynthesis in iRBD and PD with RBD, also supported the similarity between iRBD and PD. SH-SY5Y neuroblastoma cells stimulated with staurosporine is regarded as a classic cellular widely used to study Parkinson's disease 31 , the increase of staurosporine biosynthesis observed in our study might indicate the toxicity of staurosporine would active pathogenic autophagy with respect to dopaminergic cell loss 32 , resulting in the pathogenesis of RBD and PD.…”
Section: Discussionmentioning
confidence: 57%
“…For the functional prediction, the overlapping pathway, enriched staurosporine biosynthesis in iRBD and PD with RBD, also supported the similarity between iRBD and PD. SH-SY5Y neuroblastoma cells stimulated with staurosporine is regarded as a classic cellular widely used to study Parkinson's disease 31 , the increase of staurosporine biosynthesis observed in our study might indicate the toxicity of staurosporine would active pathogenic autophagy with respect to dopaminergic cell loss 32 , resulting in the pathogenesis of RBD and PD.…”
Section: Discussionmentioning
confidence: 57%
“…For the functional prediction, the overlapping pathway, enriched staurosporine biosynthesis in iRBD and PD with RBD, also supported the similarity between iRBD and PD. Staurosporine stimulated SH-SY5Y neuroblastoma cells are regarded as a classic cellular model widely used in studying PD [ 58 ], the increase of staurosporine biosynthesis observed in our study might indicate the toxicity of staurosporine would active pathogenic autophagy with respect to dopaminergic cell loss [ 59 ], resulting in the pathogenesis of RBD and PD.…”
Section: Discussionmentioning
confidence: 98%
“…The AIF/H2AX/CypA complex leads to chromatin condensation, DNA fragmentation, and chromatinolysis, which ultimately leads to cell death (Rodriguez et al., 2021). This complex is involved in various types of brain injury, such as cerebral hypoxia‐ischemia, stroke, and traumatic brain injury (Conte et al., 2021; Piao et al., 2012; Rodriguez et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…After cerebral ischemia and hypoxia, AIF and CypA combined with each other in the neurons; AIF and CypA cannot enter the nucleus without the other one (Zhu et al., 2007). The interaction of CypA with AIF is also involved in other injury types, such as neonatal brain hypoxia‐ischemia (HI) injury (Rodriguez et al., 2020), Parkinson's disease (PD) (Conte et al., 2021), and glioma cell necroptosis (Wang et al., 2022). These results suggest that CypA plays an important role in AIF‐mediated cell death, and their nuclear translocation is interdependent.…”
Section: Introductionmentioning
confidence: 99%